2000
DOI: 10.1002/1521-3757(20000616)112:12<2174::aid-ange2174>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

P6-Manganocen und P3-Cymantren: Konsequenzen des Einbaus von Phosphoratomen in Mn-koordinierende Cyclopentadienyl-Liganden

Abstract: Der Ersatz von sp2‐CR‐Fragmenten durch die isolobalen Phosphoratome kann bei Metallocenen zu einer Umkehr der Reihenfolge der Grenzorbitale führen (siehe Schema). Ein Beispiel dafür ist Hexaphosphamanganocen 1, welches den bislang bei Manganocenderivaten noch nicht beobachteten Grundzustand 2A aufweist. Die Spindichteverteilung von 1 entspricht weitgehend einem Mn‐d italicz 2‐Orbital. Deshalb ist 1 im Gegensatz zum Decamethylmanganocen nicht Jahn‐Teller‐aktiv!

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2000
2000
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
1
7
0
1
Order By: Relevance
“…There has been significant progress in the chemistry of transition‐metal complexes carrying the η 5 ‐3,5‐ t Bu 2 ‐1,2,4‐C 2 P 3 ligand 1. Although the isolobal relationship P${-\ominus \rightarrow}$ CH and diagonal relationship P/C suggest that complexes carrying this ligand should behave like the corresponding η 5 ‐cyclopentadienyl‐substituted analogues, recent work has shown that the phosphorus‐containing systems exhibit subtle differences in both bonding and reactivity 2–4. This situation suggests that further investigations could be rewarding.…”
Section: Methodsmentioning
confidence: 99%
“…There has been significant progress in the chemistry of transition‐metal complexes carrying the η 5 ‐3,5‐ t Bu 2 ‐1,2,4‐C 2 P 3 ligand 1. Although the isolobal relationship P${-\ominus \rightarrow}$ CH and diagonal relationship P/C suggest that complexes carrying this ligand should behave like the corresponding η 5 ‐cyclopentadienyl‐substituted analogues, recent work has shown that the phosphorus‐containing systems exhibit subtle differences in both bonding and reactivity 2–4. This situation suggests that further investigations could be rewarding.…”
Section: Methodsmentioning
confidence: 99%
“…Unter den bemerkenswertesten Strukturen sind das leicht gebogene (Winkel zwischen den Ebenen 16°), neutrale und diamagnetische Hexaphosphatitanocen [Ti(η 5 ‐P 3 C 2 ) 2 ],293 das paramagnetische Pentaphosphavanadocen [V(η 5 ‐P 2 C 3 )(η 5 ‐P 3 C 2 )],294 das Hexaphosphachromocen [Cr(η 5 ‐P 3 C 2 ) 2 ],295 das Hexaphosphamanganocen [Mn(η 5 ‐P 3 C 2 ) 2 ],296 das einen ungewöhnlichen 2 A‐Grundzustand hat, sowie der Tripeldecker [(η 5 ‐P 3 C 2 )Sc(μ‐ 33 )Sc(η 5 ‐P 3 C 2 )] mit 22 Valenzelektronen 297. Weitere Arbeiten umfassen die Synthese von Ga‐, In‐ und Tl‐Derivaten298, 299 sowie (η 5 ‐P 3 C 2 )‐Metall‐Carbonyl‐Komplexen,300 die außerdem Gegenstand theoretischer Studien waren 296. 299, 301, 302 Aus den Rechnungen wurde u. a. geschlossen, dass der Diamagnetismus des Hexaphosphatitanocens auf eine signifikante Rückbindung vom Ti‐Zentrum in das LUMO des P 3 C 2 ‐Ringsystems unter Bildung einer δ‐Bindung zurückzuführen ist.…”
Section: Besondere Elektronenkonfigurationenunclassified
“…Despite the striking analogies between the cyclopentaphosphide ion P 5 − and the ubiquitous cyclopentadienyl ligand and its complexes [Cp*( η 5 ‐P 5 ) Fe]3 and ferrocene it should not be overlooked that according to quantum chemical calculations the species “FeP 10 ”4 has nothing in common with the familiar class of ferrocenes or oligophosphaferrocenes. Recently it was pointed out by Zenneck et al that the introduction of six phosphorus atoms into a manganocene skeleton affords a low‐spin sandwich complex with an electronic structure different to that of decamethylmanganocene, and consistently the authors stated, that an analogy between P and C is no longer given, if formally analogous compounds differ significantly in their reactivities, spectra or molecular structures 5. Accordingly, the olefin‐like behavior of the phosphaalkenes crucially depends on the polarity (P δ + C δ − ) of the P=C double bond as anticipated by Pauling's electronegativies.…”
Section: Introductionmentioning
confidence: 99%